Dogmatism in Science and Medicine: How Dominant Theories Monopolize Research and Stifle the Search for Truth by Henry H. Bauer - Josephson, Brian (Journal of Scientific Exploration, 2014)
While the ridiculing of new ideas and their consequent suppression is not a new phenomenon (as for example happened with Semmelweis’s proposal that disease could be reduced if doctors who delivered babies washed their hands first), changes in the nature of scientific activity have introduced new and rather sinister aspects into the phenomenon. Bauer cites the case of a letter sent by Duesberg to the journal JAIDS, disputing the number of deaths due to AIDS in South Africa quoted in an article criticizing his stance on the subject, suggesting that in that article the number of deaths had been inflated by a factor 25 relative to the official statistics. Notwithstanding the fact that the appointed referees had made no attempt to dispute his analysis, the submission was refused publication. As Bauer points out, publication of a letter alleging serious inaccuracy in a journal article would normally be automatic, unless the allegation could be refuted, but that principle was disregarded in this case.